Validity of coupling TRACAB's Gen5 and mediacoach systems to calculate accelerations and decelerations in professional football - González-Rodenas, J.; Nevado, F.; López-Del Campo, R.; Soler-Aguinaga, A.; Agulló, F.; Moreno-Pérez, V.; Del Coso, J. (Sensors, 2025)
This study assessed the agreement between an optical video tracking system (TRACAB Gen5, Chyronhego, NY, USA) coupled with Mediacoach software (LaLiga, Spain) and accelerometry data derived from a GPS-Inertial Measurement Unit (IMU) device (GPS-IMU; Hudl, Lincoln, NE, USA) in measuring the number and intensity of accelerations (ACCs) and decelerations (DECs) during professional football matches. Data were collected from 46 LaLiga players across three seasons (2021-2024), resulting in 662 comparative match datasets, including 95,371 ACCs and 100,952 DECs recorded by the inertial unit of the GPS-IMU devices (considered as the reference criterion). The video tracking system consistently reported lower values for both ACCs (p < 0.001, d = 0.47) and DECs (p < 0.001, d = 1.17) than GPS-IMU. Despite this discrepancy, agreement between methods was very high for total ACCs (R2 = 0.954) and DECs (R2 = 0.950), as well as for moderate-level ACCs (2-4 m/s2, R2 = 0.956) and DECs (-2 to -4 m/s2, R2 = 0.944). The agreement was lower for high-intensity ACCs (>4 m/s2, R2 = 0.338) and DEC (<-4 m/s2, R2 = 0.838). In conclusion, integrating the TRACAB Gen5 optical video tracking system with Mediacoach software provides an effective method for assessing the physical load of professional football players. However, acceleration data obtained from this video tracking system should not be used interchangeably with GPS-IMU devices, as it systematically underestimates both accelerations and decelerations.